When aging meets digitisation: can urban digital technology innovations enhance the well-being of older adults? - Wu, Yajing; Zhu, Xianglei (Information Research an international electronic journal, 2025)
Introduction. With the rapid advancement of urban digital transformation in China, the significance of innovation in urban digital technology has become increasingly pronounced in the lives of elderly individuals. However, existing research on its impact remains limited. This study investigates the profound influence of urban digital technology innovation on the well-being of elderly people in Chinese cities, elucidating key mechanisms and moderating factors. Method. This study collected data on 1,317,694 digital technology innovation patents in urban areas, the level of urban digital transformation, and factors such as social support and well-being among elderly residents in Chinese cities. Empirical analysis was conducted using an OLS mixed-effects model, yielding compelling and convincing results. Results. Urban digital technology innovation significantly and positively affects the well-being of elderly individuals. The widespread adoption of digital technology broadens the horizons of the elderly, providing increased opportunities for social interaction, knowledge acquisition and health management. Furthermore, we identify urban digital transformation as a mediating factor between urban digital technology innovation and the well-being of elderly individuals. Crucial elements in this mediation encompass the establishment of a digital society, efficient digital governance, and robust digital infrastructure. Intriguingly, social support, serving as a moderating variable, influences the extent to which urban digital technology innovation affects the well-being of elderly individuals. Conclusion. Our study highlights the crucial role of urban digital innovation in enhancing elderly well-being. It offers valuable insights for policymakers to promote digital inclusion, social support, and sustainable urban development strategies that benefit older adults.